Relation between common polymorphisms in genes related to inflammatory response and colorectal cancer - Theodoropoulos, George (Baishideng Publishing Group Co., Limited, 2006)
AIM: To investigate the association between common single nucleotide polymorphisms (SNPs) in inflammatory response-related genes such as interleukin (IL)-6, IL-8, tumor necrosis factor α (TNFα), peroxisome proliferators-activated receptor γ (PPARγ), intercellular adhesion molecule-1 (ICAM-1) and the risk of colorectal cancer (CRC) in a group of Greek patients. METHODS: The study group consisted of 222 CRC patients and 200 healthy controls. Genotyping was performed using allele-specific PCR of PRC-RFLP and the results were confirmed by sequencing. We studied the association of SNPs in the IL-6 (-174G > C), IL-8 (-251T > A), TNFα (-308G > A), ICAM-1 (R241G and K469E), and PPARγ (Pro12Ala) genes and the risk of CRC. RESULTS: The IL-6 -174G, R241 and K469 alleles of ICAM-1 were associated with increased risk of CRC (OR = 1.77, 95% CI: 1.34-2.34; OR = 1.83, 95% CI: 1.23-2.72; and OR = 1.35, 95% CI: 1.03-1.77 respectively). The IL-8 and TNFα polymorphisms had no effect. Whereas the PPARγ Pro12 genotype was associated with increased risk of disease (OR = 1.78, 95% CI: 1.25-2.49). CONCLUSION: The association between common SNPs in immunologic response-related genes and CRC is reported in the present study. Apart from shedding light on the mechanisms of malignancy initiation and progression, SNPs may improve appropriate screening for sub-populations at risk.